Papel da atividade simpática renal na hipertensão arterial provocada pela hiperuricemia - Moura, Quézia Pires de (2008)
The pathophysiology mechanisms involving hyperuricemia and arterial hypertension are still unknown. With the aim of contributing to the knowledge of pathophysiology mechanism that involves the relationship between hiperuricemia and arterial hypertension this study was carried out to observe if renal sympathetic activity (RSA) is involved. Wistar male rats (250g) were divided in control and experimental groups. Each one of these groups was divided in the following subgrups (n=6): control (CTRL); treated with oxonic acid (OA) 2% (AOX); CTRL submitted to bilateral renal denervation (CTRL DENS); and AOX submitted to bilateral renal denervation (AOX DENS). The animals were placed in metabolic cages by 3 and 7 weeks to collect daily urine samples and the OA treatment was implemented. The basal values of mean arterial pressure (MAP) and heart rate (HR) were measured at the end of the OA treatment period. The estimate role of RSA was accessed through acute extracellular volume expansion (5% of body weigh) that produces a sympathetic withdraw. For that, the animals were submitted i.v. saline infusion (55 L/min) for 2 hours. After that period of stabilization, urine samples were collected over two 10 min of control (C1e C2), 3 expansion (E1, E2, E3), and 3 recovery periods. On the recovery periods (R1, R2, R3), the i.v. saline infusio was returned to the control rate (55 L/min). Subsequetly, samples of blood were collected to measure the plamatic concentrations of uric acid (UA) and creatinin. Under general anestesia, the animals were sacrificed and both kidneys removed to normalize the urine flow and sodium excretion, and subsequent histology. The results showed that the rats treated with OA presented increase in the plamatic concentration of UA (mg/dL) when compared with control animals (AOX 1 ± 0.06 mg/dL; AOX DESN 1 ± 0.1 mg/dL; CTRL 0.8 ± 0.08; CTRL DENS 0.7 ± 0.08; p <0.05). The accumulated values (3 weeks) of the daily excretion of sodium showed that the AOX and AOX DESN rats excreted smaller amount of urinary sodium when compared with CTRL animals (15 ± 2.6 vs 44 ± 5.0 mEq; p <0.01 and 27 ± 4.8 vs 44 ± 5.0 mEq; p <0.05). After 7 weeks of treatment, the basal values of MAP were higher in the AOX when compared to the CTRL group (120 ± 3 vs 102 ± 2 mmHg; p <0.01). The renal denervation prevented 14 this elevation in MAP (AOX DESN: 101 ± 0.7; p <0.01). Compared to the CTRL (141 ± 18.3 µL/min/g of kidney), the AOX group presented increase (27 ± 2.6 µL/min/g; p <0.01) in the urinary flow rate and in sodium excretion (NaEx) (16± 0,8 vs 10±1,8 µEq/min/g; p<0.05), and especially if compared to the AOX DESN group (141±18,3 vs 27±2,6 µL/min/g; p<0.01 e 14± 3,1 vs 3±0,2 µEq/min/g; p<0.01). When compared with the CTRL, the AOX group presented increase in the plasma concentration of creatinin (0.82 ± 0.05 vs 0.66 ± 0.04 mg/dL; p <0.05). The AOX and AOX DESN showed an apparent hypertrophy of the afferent artery, increase of intertubullar extracelullar matrix and glomerullar hypertrophy. The principal result of this study was the increase of SRA in rats that deveped arterial hypertension due to hyperuricemia. The SRA and sodium retention could be a major responsible for the hypertension once the bilateral renal denervation prevented the sodium retension and the augment of arterial hypertension.